Characterization of minerals, metals, and materials 2016 proceedsing of a symposium sponsored by the Materials Characterization Committee of the Extraction and Processing Division of the Minerals, Metals & Materials Society (TMS) held during TMS 2016, 145th Annual Meeting & Exhibition, February 14-18, Downtown Nashville, Tennessee Music City Center - Ikhmayies, Shadia Jamil (Wiley, 2016)
An authoritative collection, written by experts from around the world. The articles centre on materials characterisation, extraction, processing, corrosion, welding, solidification and method development